Frequency, socio-economic characteristics, and risk factors of oral cavity parasites in diabetes mellitus patients from Lorestan Province, Iran; a case-control study - Masoori, Leila; Baharvand, Parastoo; Khalaf, Amal Khudair; Selahbarzin, Behnoush; Sakifar, Fatemeh; Mahmoudvand, Hossein (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundNumerous studies identify diabetes mellitus (DM) as one of the most significant risk factors for the development of periodontal diseases (gum diseases). Individuals with diabetes experience gingival destruction more rapidly and severely due to the accumulation of microbial plaque in the mouth. Entamoeba gingivalis and Trichomonas tenax are parasites commonly found in the human oral cavity. This study aims to determine, the frequency, socio-economic characteristics, and risk factors of E. gingivalis and T.tenax in DM patients from Lorestan Province, Iran as a case-control study.MethodsThe current case-control study involved 500 DM patients who were referred to health centers in Lorestan province, Iran between December 2022 and June 2024. Furthermore, a control group comprising 500 healthy persons without DM (non-DM) who were referred to health centers during the same study period was incorporated into the research. The prevalence of parasites in the oral cavity was determined using microscopic analysis and conventional polymerase chain reaction (PCR) techniques. A questionnaire was administered to collect demographic information, including age, gender, place of residence, education level, occupation, monthly income, tooth brushing practices, and mouthwash usage.ResultsOut of a total of 500 DM patients, 136 (27.2%) and 146 (29.2%) patients had the oral cavity parasites (E. gingivalis and T. tenax) by microscopic and PCR analysis, respectively. While, in non-DM, 61 (12.2%) and 65 (13.0%) tested positive for parasites using microscopic and PCR methods, respectively (P<0.001). Among several factors, income (P = 0.001, OR = 5.491, 95% CI: 4.089 to 9.723), place of residence (P = 0.006, OR = 1.982, 95% CI: 1.222), education (P = 0.002, OR = 3.577 (1.618, 5.907)), and use mouthwash demonstrated a significant protective effect on the oral cavity parasites.ConclusionThis research for the first time in Iran highlighted a considerable prevalence of oral cavity parasites in DM patients in Lorestan province, Western Iran. Dental professionals should maintain a heightened awareness of these risk factors to effectively identify and address oral health challenges within this population, thereby reducing the incidence of oral diseases and infections.